2013
DOI: 10.1097/hjh.0b013e32835ed5d0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between insomnia symptoms and hypertension using United States population-level data

Abstract: Insomnia symptoms coupled with short sleep time may be positively related to hypertension, but the lack of association with objective hypertension measures suggests that there may be no true relationship present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 28 publications
0
28
1
Order By: Relevance
“…duration lasting less than 5 h or less than 7 h is an environmental risk factor for HT in middle-aged subjects, the majority of studies performed in the insomniac elderly concluded that sleep duration is not associated with prevalent HT before or after adjustment for confounding variables. 8,15,23,[30][31][32] In 8,757 participants in the Arteriosclerosis Risk in Communities (ARIC) study aged 45 to 69 years, 29 the difficulty of falling asleep, sleep maintenance complaints, and tiredness reported at the final awakening were the most important factors predicting cardiovascular risk 6.3 years later, but they did not predict hypertension. In a recent paper on 12,643 participants with and without insomnia, 33 no association was observed between objective hypertension measures and sleep duration, suggesting the lack of a true relationship in older patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…duration lasting less than 5 h or less than 7 h is an environmental risk factor for HT in middle-aged subjects, the majority of studies performed in the insomniac elderly concluded that sleep duration is not associated with prevalent HT before or after adjustment for confounding variables. 8,15,23,[30][31][32] In 8,757 participants in the Arteriosclerosis Risk in Communities (ARIC) study aged 45 to 69 years, 29 the difficulty of falling asleep, sleep maintenance complaints, and tiredness reported at the final awakening were the most important factors predicting cardiovascular risk 6.3 years later, but they did not predict hypertension. In a recent paper on 12,643 participants with and without insomnia, 33 no association was observed between objective hypertension measures and sleep duration, suggesting the lack of a true relationship in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 The PSQI questionnaire consists of 19 individual items that generate 7 component scores: subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleep disturbances, use of sleeping pills, and daytime dysfunction. According to previously published data, 30 participants were divided into 2 groups: good sleepers (GS) with a score < 5 and poor sleepers (PS) with a score ≥ 5.…”
Section: Self-assessment Of Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, although many studies find that insomnia predicts increased incidence of hypertension, 4 some do not [6][7][8] One potential explanation may be the fact that the underlying mechanism of risk between insomnia and hypertension remains poorly understood, and studies may therefore find varying results based on differing variables used. Vgontzas et al 9 have argued that risk for hypertension may be conferred through decreased sleep duration, as well as in conjunction with insomnia, with an adjusted odds ratio estimated at 5.12, which is significantly higher than that for insomnia alone (range estimated between 1.05 and 2.24).…”
Section: Introductionmentioning
confidence: 99%
“…Its reliability and validity were previously evaluated (14). It contains 19 self-rating questions and evaluates seven domains of sleep including latency, duration, quality, efficiency, disturbances, use of medication for sleep, and day time dysfunction (15). A high score indicates multiple sleep complaints.…”
Section: Methodsmentioning
confidence: 99%